2014
DOI: 10.1007/s10531-014-0755-x
|View full text |Cite
|
Sign up to set email alerts
|

Acacia trees on the cultural landscapes of the Red Sea Hills

Abstract: This paper examines interactions between five pastoral nomadic culture groups of the Egyptian and Sudanese Red Sea Hills and the acacia trees Acacia tortilis (Forssk.) Hayne subsp. tortilis and subsp. raddiana growing in their arid environments. A. tortilis is described as a keystone species both ecologically and culturally: the trees play such critical roles in ecosystems and social groups that their removal would greatly impact both systems. Interviews in the field with the Semitic, Arabic-speaking Ma'aza an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…The northern areas of the ED, and in particular Ma'aza area, are more affected by sedentarization and abandonment (Hobbs et al. ) although domestic animals still roam there. In parts of RSH, particularly more remote areas, traditional nomadism is still practiced (see Andersen et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The northern areas of the ED, and in particular Ma'aza area, are more affected by sedentarization and abandonment (Hobbs et al. ) although domestic animals still roam there. In parts of RSH, particularly more remote areas, traditional nomadism is still practiced (see Andersen et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Hobbs et al. ). Current evidence suggests this important species exhibits high mortality and low recruitment, which threatens both regional biodiversity and the livelihoods of people dependent upon it (Ward and Rohner ; Andersen and Krzywinski ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the earliest records which describes the medicinal properties of EBN was the Ben Cao Gang Mu written by Li Shizhen . To date, the consumption of EBN is believed by the Chinese community to be able to bring about effects: dissolving phlegm, relieving gastric troubles, aiding renal functions, raising libido, enhancing complexion, relieving asthma, suppressing cough, curing tuberculosis, curing hematemesis, nourishing the lungs, speeding up recovery after surgery, strengthening the immune system, improving the growth of children, increasing energy and metabolism, and improving concentration . In the last century, many scientists have devoted their efforts to the study of the health effects brought about by the consumption of EBN.…”
mentioning
confidence: 99%
“…1). Moreover, it has been demonstrated that gazelles have an important role in the distribution of acacia trees, which are considered keystone flora species in the Arava Valley (Munzbergova and Ward 2002) and in other desert lands (Hobbs et al 2014). It would seem that by eco-engineering the soil for antlions, gazelles also indirectly help in the pollination of acacia trees, and thus help themselves in a two-step non-trophic/trophic fashion (Fig.…”
Section: Discussionmentioning
confidence: 99%